Dual regulation of the levels and function of Start transcriptional repressors drives G1 arrest in response to cell wall stress - Mihai Spiridon-Bodi; Cristina Ros-Carrero; J. Carlos Igual; Mercè Gomar-Alba (Cell Communication and Signaling)
Abstract Background Many different stress signaling pathways converge in a common response: slowdown or arrest cell cycle in the G1 phase. The G1/S transition (called Start in budding yeast) is a key checkpoint controlled by positive and negative regulators. Among them, Whi7 and Whi5 are transcriptional repressors of the G1/S transcriptional program, yeast functional homologs of the Retinoblastoma family proteins in mammalian cells. Under standard conditions, Whi7 plays a lesser role than Whi5 in Start inhibition. However, under cell wall stress, Whi7 is induced and plays a more important role in G1/S control. In this work, we investigated the functional hallmarks of Whi7 and Whi5, which determine their strength as Start inhibitors under cell wall stress. Methods The response of Saccharomyces cerevisiae to Calcofluor White was investigated to characterize the regulation and function of Whi7 and Whi5 under cell wall stress. To control their protein levels, we used dose-dependent β-estradiol-induced expression and auxin-induced degron protein fusions. We also performed Chromatin Immunoprecipitation assays to investigate Whi7 and Whi5 association with Start promoters and scored cell cycle arrest and re-entry using cell microscopy assays. Results We found that cell wall stress promoted the specific upregulation of the Whi7 Start repressor. First, although cell wall stress increases Whi7 protein levels, this is not the only determinant behind the Whi7 function in promoting G1 arrest. Indeed, artificial induction of Whi5 at the same protein level resulted in a lower G1 block. Second, under cell wall stress, Whi7 was specifically recruited to SBF-target promoters, independent of the increase in its protein levels or cell cycle stage. Finally, we found that Whi7 protein instability further increased during cell wall stress and that Whi7 degradation triggered advanced cell cycle re-entry. Conclusions Here, we show that cell wall stress signaling specifically enhances Whi7 function as a Start transcriptional repressor. Importantly, we identified new Whi7-specific regulatory mechanisms that do not operate in the Whi5 repressor. Our results indicate that cells may benefit from stress-specific repressors to ensure the stress-induced G1 arrest and that Whi7 rapid degradation may be particularly important to resume cell cycle upon adaptation.